Effect of Accuracy Exercises Against the accuracy of top service in volleyball games - Oong Liawanto (Journal of Physical Education and Sport Science, 2019)
This research is motivated by the lack of satisfactory top service proven by being inaccurate in directing service to the opponent's field, serving out of the field or being easily accepted by the opponent because it is aimed directly at the opponent without having to change direction from the opponent. The purpose of this study was to determine the effect of accuracy training on the accuracy of top service in volleyball games at male volleyball extracurricular members at SMK Negeri 1 Japara. This research is an experimental research. The population in this study were male extracurricular participants at SMK Negeri 1 Japara which numbered 30 students. The sampling technique used was total sampling by determining the population to be used as research samples so that male extracurricular members were obtained at SMK Negeri 1 Japara, amounting to 30 students. The data collection technique used is the top service test. The data analysis technique in this study is the normality test and hypothesis test (z test) which is used to determine the effect of accuracy training on the accuracy of top service in volleyball games on male volleyball extracurricular members at SMK Negeri 1 Japara. Based on the statistical calculation obtained by Z Hit (13,213)> Z daf (2,35) then the Hi received means that there is an effect of accuracy training on the accuracy of top service in volleyball games at male volleyball extracurricular members at SMK Negeri 1 Japara. The conclusion of this study is that the accuracy training influences the accuracy of the top service in volleyball games for male volleyball extracurricular members at SMK Negeri 1 Japara.